Study on Clitoria ternatea extracts doped sol-gel coatings for the corrosion mitigation of mild steel - Noorliza Azwani Muhamad Ghuzali (Applied Surface Science Advances, 2021)
The study is focused on incorporating Clitoria ternatea extracts (isolated using water (WE) and ethanol (EE) solvents) into the sol-gel coating for the corrosion mitigation of mild steel. Clitoria ternatea extracts were characterized through Fourier transform infrared spectroscopy (FTIR) and phytochemical analysis. Based on the results obtained, it was remarked that the ethanol extract contained more substantial antioxidant properties compared to the water extract. Corrosion mitigation capability of sol-gel coatings doped with extracts of Clitoria ternatea (0, 25, 50, 75 and 100 ppm) on mild steel was assessed using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization. According to the electrochemical impedance spectroscopy (EIS) data, ethanol extract (EE) doped sol-gel coating at 75 ppm offered higher inhibition efficiency (89.6%) in comparison to the water extract. Scanning electron microscopy (SEM) images affirmed improved surface morphology of mild steel substrates in the presence of both inhibitors. It was revealed that the coated mild steel with Clitoria ternatea extracts provide a smooth surface compared to the untreated mild steel substrate.